Analisis Tingkat Pendidikan dengan Tingkat Pengetahuan Ibu Primigravida Trimester III Tentang Perawatan Payudara Pada Masa Nifas - Dyah Muliawati (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2022)
Breast milk is a fluid produced by the breast glands since pregnancy and is a natural food that contains the best nutrients for babies. WHO has a target by 2025, the prevalence of exclusive breastfeeding reaches 50%, meaning that until now the target has not been achieved. The level of education is a predisposing factor that affects the level of human knowledge. The purpose of the study was to determine the relationship between the level of education and the level of knowledge of primigravida mothers in the third trimester about breast care in the puerperium. The research method is an analytical survey with a cross-sectional approach. A large sample of 30 respondents with cluster proportional random sampling technique. The research instrument is a questionnaire with a chi-square statistical test. The results of the statistical test showed a value of p = 0.003, so it can be concluded that there is a relationship between the level of maternal education and the level of knowledge of primigravida mothers in the third trimester about breast care in the puerperium. Keywords : Education, Knowledge, Breast Care, Exclusive breastfeeding